A lithium ion battery negative electrode sheet and preparation method thereof and battery

By designing a multi-layer structure in the negative electrode sheet of a lithium-ion battery, using the combination of soft carbon and silicon-carbon materials, the expansion problem of silicon-based materials is alleviated, the electrochemical performance and safety of the battery are improved, and the lithium-ion battery is solved. The problem of poor circulation stability of the negative electrode material.

CN118763179BActive Publication Date: 2024-12-31JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411197043.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-31
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The silicon-based negative electrode material in lithium-ion batteries is prone to volume expansion during charging and discharging, resulting in damage to the electrode structure, and poor circulation stability, which limits its commercial application.

Method used

Design a negative electrode sheet, by providing a multi-layer structure on both sides of the current collector thickness direction, including a first active material layer (soft carbon), a second active material layer (silicon carbon material) and a third active material layer (surface A hard carbon material coated with soft carbon) and provides a lateral and longitudinal buffer space by controlling the width and thickness relationship of each layer to slow down the expansion and side reaction of silicon.

Benefits of technology

It effectively reduces the structural damage of the negative electrode plate during charging and discharging, improves the electrochemical performance, safety performance and service life of the battery, and enhances the stability and lithium ion transmission capabilities of the electrode plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118763179B_ABST
    Figure CN118763179B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode plate for a lithium-ion battery, a preparation method thereof, and a battery. The negative electrode plate comprises a current collector, and a first active material layer, a second active material layer, and a third active material layer sequentially arranged on at least one side surface of the current collector in the thickness direction; the width of the second active material layer is smaller than the width of the first active material layer, and the third active material layer covers the first active material layer and the second active material layer at least in the width direction of the current collector; the first active material layer comprises a first active material, which is soft carbon; the second active material layer comprises a second active material, which is a silicon-carbon material; the third active material layer comprises a third active material, which is a hard carbon material with soft carbon coated on the surface. The negative electrode plate can effectively improve the electrochemical performance, safety performance, and service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery negative electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] As an important component of modern energy storage technology, lithium-ion batteries have been widely used in electric vehicles, smart phones, drones, laptops, electronic watches, game consoles, aerospace and other fields due to their high voltage, high energy density, good cycle performance and low self-discharge. With the rapid development of the new energy vehicle industry and the urgent need for energy conservation and emission reduction around the world, the market demand for lithium-ion batteries continues to grow, and the requirements for battery performance are also increasing.

[0003] In lithium-ion batteries, the negative electrode material is one of the key factors that determine battery performance. Among them, silicon-based negative electrode materials are ideal negative electrode materials for lithium-ion batteries due to their ultra-high theoretical specific capacity, suitable voltage platform and low cost. However, silicon-based negative electrode materials are prone to volume expansion during the charging and discharging process, resulting in damage to the electrode structure, and excessive side reactions caused by direct contact between silicon and electrolytes, which causes a decrease in capacity. These problems lead to poor cycle stability and limit their commercial application.

[0004] At present, most of the improvement methods are based on the material itself, such as compounding silicon with carbon materials to improve the performance of lithium-ion batteries. There has been no report on improving the composition of the negative electrode material and the structure of the negative electrode sheet at the same time to improve the energy density, cycle stability and safety of lithium-ion batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In order to solve the above technical problems, the present invention provides a lithium ion battery negative electrode plate and a preparation method thereof and a battery. The negative electrode plate provided by the present invention reduces the expansion rate of silicon, slows down the structural damage of the negative electrode plate during the charging and discharging process, and can effectively improve the electrochemical performance, safety performance and service life of the battery.

[0008] Solutions for solving problems

[0009] The present invention solves the above technical problems through the following technical solutions:

[0010] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector, and a first active material layer, a second active material layer and a third active material layer sequentially arranged on at least one side surface of the current collector in a thickness direction;

[0011] The second active material layer has a width smaller than that of the first active material layer, and the third active material layer covers the first active material layer and the second active material layer at least in the width direction of the current collector;

[0012] The first active material layer includes a first active material, and the first active material is soft carbon;

[0013] The second active material layer includes a second active material, and the second active material is a silicon-carbon material;

[0014] The third active material layer includes a third active material, and the third active material is a hard carbon material with soft carbon coated on the surface.

[0015] Preferably, on both sides of the current collector in the width direction, there is a preset width difference between the edge of the first active material layer and the edge of the second active material layer.

[0016] Preferably, along the width direction of the current collector, the thickness of the third active material layer gradually decreases from a preset position to the edge of the negative electrode sheet, and the projection of the preset position in the thickness direction of the current collector is located between the edge of the first active material layer and the edge of the second active material layer.

[0017] Preferably, on both sides of the current collector in the width direction, the preset width difference on both sides of the second active material layer is equal; and the negative electrode sheet satisfies at least one of the following relationships:

[0018] L 差 =1 / 2(L1-L2);

[0019] L1>L 3顶 >L2;

[0020] L 3底 >L1;

[0021] Among them, the L 差 is the preset width difference; L1 is the width of the first active material layer; L2 is the width of the second active material layer; 3顶 is the top width of the third active material layer; 3底 is the bottom width of the third active material layer.

[0022] Preferably, the D50 of the first active substance is in the range of 5 to 25 μm.

[0023] Preferably, the D50 of the second active substance is in the range of 3 to 15 μm.

[0024] Preferably, the D50 of the third active substance is in the range of 2-18 μm.

[0025] Preferably, the current collector is selected from one or more of copper foil, aluminum foil and nickel foil.

[0026] Preferably, the soft carbon in the first active material layer and the soft carbon in the third active material layer are each independently selected from one or more of carbon fibers, carbon microspheres, graphitized mesophase carbon microbeads, petroleum coke and needle coke.

[0027] Preferably, the silicon-carbon material is selected from silicon-carbon materials containing 20% ​​to 40% silicon.

[0028] Preferably, the hard carbon is selected from one or more of resin carbon, organic polymer pyrolytic carbon and carbon black.

[0029] Preferably, the first active material layer further includes a first conductive agent and a first binder, and the mass ratio of the first active material to the first conductive agent to the first binder is (96-98): (0.5-1.5): (1-3).

[0030] Preferably, the second active material layer further includes a second conductive agent and a second binder, and the mass ratio of the second active material to the second conductive agent to the second binder is (94-97): (1.5-3.5): (1-3).

[0031] Preferably, the third active material layer further includes a third conductive agent and a third binder, and the mass ratio of the third active material to the third conductive agent to the third binder is (96-98): (0.5-1.5): (1-3).

[0032] Preferably, the first conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0033] Preferably, the first binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0034] Preferably, the second conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0035] Preferably, the second binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0036] Preferably, the third conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0037] Preferably, the third binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0038] The second aspect of the present invention provides a method for preparing the negative electrode sheet according to the first aspect of the present invention, comprising the following steps:

[0039] S0: preparing a slurry of the first active material layer: mixing the first active material, the first conductive agent, and the first binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry of the first active material layer;

[0040] Preparing a slurry for the second active material layer: mixing the second active material, the second conductive agent, and the second binder in a mass ratio of (94-97): (1.5-3.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the second active material layer;

[0041] Preparing a slurry for the third active material layer: mixing the third active material, the third conductive agent, and the third binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the third active material layer;

[0042] S1: coating the prepared slurry of the first active material layer onto the current collector, drying and rolling after coating to obtain an intermediate structure A;

[0043] S2: coating the prepared second active material layer slurry onto the intermediate structure A obtained in step S1, and drying and rolling after coating to obtain the intermediate structure B;

[0044] S3: coating the prepared third active material layer slurry onto the intermediate structure B obtained in step S2. After coating, drying and rolling are performed to obtain the negative electrode sheet.

[0045] Preferably, the compaction density of the first active material layer is 1.0-1.3 g / cm 3 .

[0046] Preferably, the compaction density of the second active material layer is 1.3-1.5 g / cm 3 .

[0047] Preferably, the compaction density of the third active material layer is 1.0-1.3 g / cm 3 .

[0048] Preferably, the compaction density of the negative electrode plate is 1.5-1.6 g / cm 3 .

[0049] A third aspect of the present invention provides a battery, comprising the negative electrode sheet according to the first aspect of the present invention or the negative electrode sheet prepared by the preparation method according to the second aspect of the present invention.

[0050] Effects of the Invention

[0051] 1. The negative electrode plate provided by the present invention reduces the expansion rate of silicon, thereby slowing down the structural damage of the negative electrode plate during the charging and discharging process, and can effectively improve the electrochemical performance, safety performance and service life of the battery.

[0052] 2. The present invention provides lateral and longitudinal buffer space for the volume expansion of silicon, thereby suppressing the expansion of silicon in multiple directions, thereby reducing the expansion rate of the pole piece, and can better overcome the structural collapse caused by silicon expansion, effectively improving the stability and service life of the pole piece.

[0053] Relieve the longitudinal expansion of silicon: By selecting soft carbon as the active material of the first active material layer in the negative electrode, the downward squeezing force of the silicon expansion in the silicon-carbon material of the second active material layer can be alleviated, and the electron conduction and lithium ion transmission capabilities can be improved.

[0054] Alleviate the lateral expansion of silicon: By controlling the width of the second active material layer to be narrower than the width of the first active material layer and the top width of the third active material layer, and providing slopes on both sides of the third active material layer to provide space for the lateral expansion of silicon, the bulging edge caused by the lateral expansion of silicon particles at the edge of the second active material layer can be effectively alleviated.

[0055] 3. By using a hard carbon material coated with soft carbon on the surface as the active material of the third active material layer, it is possible to reduce the direct contact between silicon and the electrolyte to reduce the occurrence of side reactions, and at the same time, it is also possible to improve the rapid deintercalation of lithium ions and the electrical performance and high-temperature cycle performance of the battery prepared using the negative electrode sheet.

[0056] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0058] Figure 1 Schematic diagram of the cross-sectional structure of the intermediate structure A in some embodiments of the present invention;

[0059] Figure 2Schematic diagram of the cross-sectional structure of the intermediate structure B in some embodiments of the present invention;

[0060] Figure 3 Schematic diagram of the cross-sectional structure of the negative electrode sheet in some embodiments of the present invention.

[0061] Description of Reference Numerals

[0062] 1. Current collector;

[0063] 2. a first active material layer;

[0064] 3. A second active material layer;

[0065] 4. The third active material layer. DETAILED DESCRIPTION

[0066] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is a detailed description by listing specific embodiments. Wherein, the drawings are not necessarily drawn to scale, and local features can be enlarged or reduced to more clearly show the details of local features. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional experimental conditions. Reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0067] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0068] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0069] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0070] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0071] In the present invention, the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "height", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like to indicate directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of simplified description of the present invention, and do not indicate that the referred device or element must have a specific direction, be constructed and operated in a specific direction, and should not be understood as a limitation to the present invention.

[0072] In the present invention, the terms "first" and "second" are only used for the purpose of clear description and cannot be understood as the relative importance of the indicated features or the number of the indicated technical features. Therefore, the features defined as "first" and "second" can explicitly include at least one of the features. In the description of the present invention, "multiple" means at least two, such as two, three, etc.; "several" means at least one, such as one, two, three, etc., unless otherwise clearly and specifically defined.

[0073] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0074] The first aspect of the present invention provides a negative electrode plate, see Figure 3 As shown, the negative electrode sheet includes a current collector 1, and a first active material layer 2, a second active material layer 3 and a third active material layer 4 sequentially arranged on at least one side surface of the current collector 1 in the thickness direction;

[0075] The width of the second active material layer 3 is smaller than that of the first active material layer 2 , and the third active material layer 4 covers the first active material layer 2 and the second active material layer 3 at least in the width direction of the current collector 1 ;

[0076] The first active material layer 2 includes a first active material, and the first active material is soft carbon;

[0077] The second active material layer 3 includes a second active material, and the second active material is a silicon-carbon material;

[0078] The third active material layer 4 includes a third active material, and the third active material is a hard carbon material with soft carbon coated on the surface.

[0079] Since soft carbon has a lower hardness than graphite and has better conductivity than graphite, by using soft carbon as the active material in the first active material layer, the downward squeezing force of the silicon expansion in the silicon-carbon material of the second active material layer can be alleviated, and the electron conduction and lithium ion transmission capabilities can be improved; by using a hard carbon material with a surface coated with soft carbon in the third active material layer, the direct contact between silicon and the electrolyte can be reduced to reduce the occurrence of side reactions, and the rapid deintercalation of lithium ions and the electrochemical performance, safety performance and service life of the battery can be improved.

[0080] The above-mentioned "at least one side surface in the thickness direction of the current collector" refers to one surface of the current collector along its own thickness direction, or two surfaces of the current collector along its own thickness direction. The "surface" here can be the entire area of ​​the current collector or a partial area of ​​the current collector. This application has no special restrictions on this, as long as the purpose of this application can be achieved.

[0081] In some embodiments, there is a preset width difference between the edge of the first active material layer 2 and the edge of the second active material layer 3 on both sides of the width direction of the current collector 1. The preset width difference mainly plays a supporting role for the third active material layer 4 and alleviates the lateral expansion of silicon particles at the edge of the second active material layer 3 along the width direction, thereby improving the electrochemical performance, safety performance and service life of the battery.

[0082] In some embodiments, along the width direction of the current collector 1, the thickness of the third active material layer 4 gradually decreases from a preset position to the edge of the negative electrode sheet, and the projection of the preset position in the thickness direction of the current collector 1 is located between the edge of the first active material layer 2 and the edge of the second active material layer 3.

[0083] For example, the preset position is located at Figure 3 When the preset position is at position A, the preset position is close to the left edge of the negative electrode sheet, and the thickness of the third active material layer 4 gradually decreases from the preset position A to the left edge of the negative electrode sheet; for another example, the preset position is located at Figure 3 When it is at position B, the preset position is close to the right edge of the negative electrode sheet, and the thickness of the third active material layer 4 gradually decreases from the preset position B to the right edge of the negative electrode sheet.

[0084] The "left side" refers to the vertical direction of the eyes of a person skilled in the art. Figure 3The left side along the width direction of the current collector 1; the "right side" is the vertical direction observed by the eyes of a person skilled in the art. Figure 3 , along the right side in the width direction of the current collector 1.

[0085] In some embodiments, the edge of the negative electrode sheet is the edge of the current collector 1 .

[0086] In certain embodiments, the distance difference between the edge of the first active material layer 2 and the edge of the second active material layer 3 is the “preset width difference”.

[0087] In certain embodiments, Figure 3 As shown, the cross-sectional profile of the third active material layer 4 is a trapezoid, wherein the bottom width of the third active material layer 4 is greater than the top width, and the cross-sectional profile is a cross-sectional profile along the width direction of the current collector 1. The cross-sectional profile of the third active material layer 4 is a trapezoid, which can better restrain and stabilize the first active material layer 2 and the second active material layer 3, thereby improving the electrochemical performance, safety performance and service life of the battery.

[0088] In some embodiments, on both sides of the current collector 1 in the width direction, the preset width difference on both sides of the second active material layer 3 is equal.

[0089] In certain embodiments, the negative electrode sheet satisfies: L 差 =1 / 2(L1-L2); where L 差 is the preset width difference; L1 is the width of the first active material layer 2 ; and L2 is the width of the second active material layer 3 .

[0090] In some embodiments, the negative electrode sheet satisfies: L1>L 3顶 > L2; wherein L1 is the width of the first active material layer 2; L2 is the width of the second active material layer 3; 3顶 is the top width of the third active material layer 4. The width of the second active material layer 3 is narrower than the width of the first active material layer 2 and the top width of the third active material layer 4, which can effectively alleviate the bulging caused by the lateral expansion of silicon particles at the edge of the second active material layer 3 along the width direction of the current collector 1, thereby improving the electrochemical performance, safety performance and service life of the battery.

[0091] In certain embodiments, the negative electrode sheet satisfies: L 3底 >L1; wherein L1 is the width of the first active material layer 2; 3顶 is the top width of the third active material layer 4 .

[0092] In some embodiments, the D50 range of the first active substance is 5~25 μm。 further, the D50 range of the first active substance is 7~20μm, for example it can be 7.0μm、7.1μm、7.2μm、7.3μm、7.4μm、7. 5μm、7.6μm、7.7μm、7.8μm、7.9μm、8.0μm、8.1μm、8.2μm、8.3μm、8.4μm、8.5μm、8. 6μm, 8.7μm, 8.8μm, 8.9μm, 9.0μm, 9.1μm, 9.2μm, 9.3μm, 9.4μm, 9.5μm, 9.6μm, 9.7μm, 9.8μm, 9.9μm, 10.0μm, 10.1μm, 10.2μm, 10.3μm, 10.4μm, 10.5μm, 10.6μm, 1 0.7μm, 10.8μm, 10.9μm, 11.0μm, 11.1μm, 11.2μm, 11.3μm, 11.4μm, 11.5μm, 11.6μm, 11.7μm, 11.8μm, 11.9μm, 12.0μm, 12.1μm, 12.2μm, 12.3μm, 12.4μm, 12.5μm, 12.6μm, 12.7μm, 12.8μm, 12.9μm, 13.0μm, 13.1μm, 13.2μm, 13.3μm, 13.4μm, 13.5μm, 13.6μm, 13.7μm, 13.8μm, 13.9μm, 14.0μm, 14.1μm, 14.2μm, 14.3μm, 14.4μm ,14.5μm,14.6μm,14.7μm,14.8μm,14.9μm,15.0μm,15.1μm,15.2μm,15.3μm,15.4μm,15.5μm,15.6μm,15.7μm,15.8μm,15.9μm,16.0μm,16.1μm,16.2μm,16.3μm,16.4μm,16.5μm,16.6μm,16.7μm,16.8μm,16.9μm,17.0μm,17.1μm,17.2μm,17.3μm,17.4μm, 17.5μm、17.6μm、17.7μm、17.8μm、17.9μm、18.0μm、18.1μm、18.2μm、18.3μm、18.4μm、18.5μm、18.6μm、18.7μm、18.8μm、18.9μm、 19.0μm、19.1μm、19.2μm、19.3μm、19.4μm、19.5μm、19.6μm、19.7μm、19.8μm、19.9μm or 20.0μm,but not limited to the value listed, other values ​​not listed in the value range are also applicable.

[0093] In the present invention, since the active material used in the first active material layer is a soft carbon material, if the D50 of the first active material is too small, the larger the specific surface area, the stronger the activity of the material, and the material itself is easy to expand and enlarge, which has a reverse effect on the expansion of silicon in the silicon-carbon material of the second active material layer, and cannot alleviate the downward expansion force of silicon; if the D50 of the first active material is too large, its bottom layer is difficult to process, and there is a risk of debonding from the current collector layer. Within the above-mentioned D50 range of the first active material, the soft carbon material of the first active material layer can not only alleviate the downward squeezing force of the second layer of active material silicon expansion, but also reduce the risk of debonding, thereby improving the electrochemical performance, safety performance and service life of the battery.

[0094] In some embodiments, the D50 of the second active substance is in the range of 3 to 15 μm. Further, the D50 of the second active substance is in the range of 5 to 10 μm, for example, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6.0 μm, 6.1 μm, 6.2 μm, 6.3 μm, 6.4 μm, 6.5 μm, 6.6 μm, 6.7 μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm, 7.5 μm, 7.6 μm, 7.7 μm, 7.8 μm, 7.9 μm, 8.0 μm, 8.1 μm, 8.2 μm, 8.3 μm, 8.4 μm, 8.5 μm, 8.6 μm, 8.7 μm, 8.8 μm, 8.9 μm, 9.0 μm, 9.1 μm, 9.2 μm, 9.3 μm, 9.4 μm, 9.5 μm, 9.6 μm, 9.7 μm, 9.8 μm, 9.9 μm, 10.1 μm, 10.2 μm, 10.3 μm, 10.4 μm 7μm, 7.8μm, 7.9μm, 8.0μm, 8.1μm, 8.2μm, 8.3μm, 8.4μm, 8.5μm, 8.6μm, 8.7μm, 8.8μm, 8.9μm, 9.0μm, 9.1μm, 9.2μm, 9.3μm, 9.4μm, 9.5μm, 9.6μm, 9.7μm, 9.8μm, 9.9μm or 10.0μm, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0095] In the present invention, since the active material used in the second active material layer is a silicon-carbon material, if the D50 of the second active material is too small, the specific surface area is large, the surface activity of the silicon-carbon material is large, and lithium ion extraction is easier, resulting in accelerated silicon expansion, and further increased material damage; in addition, if the D50 of the second active material is too small, the material strength will be high and processing and dispersion will be difficult. Within the above-mentioned D50 range of the second active material, the silicon expansion in the silicon-carbon material can be reduced, the material damage can be reduced, the electrochemical performance, safety performance and service life of the battery can be improved, and it is easy to process.

[0096] In some embodiments, the D50 of the third active substance is in the range of 2 to 18 μm. Further, the D50 of the third active substance is in the range of 3 to 12 μm, for example, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm , 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm, 6.1μm, 6.2μm, 6.3μm, 6.4μm, 6.5μm, 6. 6μm, 6.7μm, 6.8μm, 6.9μm, 7.0μm, 7.1μm, 7.2μm, 7.3μm, 7.4μm, 7.5μm, 7.6μm, 7.7μm, 7.8μm, 7.9μm, 8.0μm, 8.1μm, 8.2μm, 8.3μm, 8.4μm, 8.5μm, 8.6μm, 8.7μm, 8.8μm, 8.9μm, 9.0μm, 9.1 μm, 9.2μm, 9.3μm, 9.4μm, 9.5μm, 9.6μm, 9.7μm, 9.8μm, 9.9μm, 10.0μm, 10.1μm, 10.2μm, 10.3 μm, 10.4μm, 10.5μm, 10.6μm, 10.7μm, 10.8μm, 10.9μm, 11.0μm, 11.1μm, 11.2μm, 11.3μm, 11.4μm, 11.5μm, 11.6μm, 11.7μm, 11.8μm, 11.9μm or 12.0μm, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] In the present invention, since the active material used in the third active material layer is a hard carbon material with soft carbon coated on the surface, if the D50 of the third active material is too small, the specific surface area is large, which is more conducive to lithium ion transmission. Therefore, the larger the specific surface area in contact with the electrolyte, the more charge is consumed by the SEI film formed during the initial charge and discharge process, and the greater the irreversible capacity loss, which will deteriorate the battery performance. In addition, it is easy to cause the material itself to expand greatly, resulting in serious damage to the material, and thus unable to alleviate the upward force of silicon expansion in the silicon-carbon material of the second active material layer. Within the D50 range of the above-mentioned third active material, the specific surface area in contact with the electrolyte can be reduced, reducing irreversible capacity loss; and the upward force of silicon expansion in the silicon-carbon material of the second active material layer can be effectively alleviated, improving the electrochemical performance, safety performance and service life of the battery.

[0098] In some embodiments, the current collector 1 is selected from one or more of copper foil, aluminum foil and nickel foil.

[0099] In certain embodiments, the current collector 1 is selected from copper foil.

[0100] In certain embodiments, the soft carbon in the first active material layer 2 is selected from one or more of carbon fibers, carbon microspheres, graphitized mesophase carbon microbeads, petroleum coke, and needle coke.

[0101] In some embodiments, the soft carbon in the first active material layer 2 is selected from petroleum coke.

[0102] In certain embodiments, the silicon-carbon material is selected from silicon-carbon materials containing 20% ​​to 40% silicon, for example, silicon-carbon materials containing 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40% silicon, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In certain embodiments, the silicon-carbon material is selected from a silicon-carbon material containing 30% silicon.

[0104] In certain embodiments, the silicon material in the silicon-carbon material is selected from silicon monoxide.

[0105] In certain embodiments, the carbon material in the silicon-carbon material is selected from graphite.

[0106] In certain embodiments, the mass ratio of graphite to silicon oxide in the silicon-carbon material is 7:3.

[0107] In certain embodiments, the soft carbon in the third active material layer 4 is selected from one or more of carbon fibers, carbon microspheres, graphitized mesophase carbon microspheres, petroleum coke, and needle coke.

[0108] In some embodiments, the soft carbon in the third active material layer 4 is selected from needle coke.

[0109] In certain embodiments, the hard carbon is selected from one or more of resin carbon, organic polymer pyrolytic carbon and carbon black.

[0110] In certain embodiments, the hard carbon is selected from resin carbon.

[0111] In certain embodiments, the third active material is a resin carbon material with needle coke coated on the surface.

[0112] In some embodiments, the first active material layer 2 also includes a first conductive agent and a first binder, and the mass ratio of the first active material to the first conductive agent to the first binder is (96~98):(0.5~1.5):(1~3), for example, 96:1:3, 96:1.5:2.5, 96.5:0.5:3, 96.5:1:2.5, 96.5:1.5:2, 97:0.5:2.5, 97:1;2, 97:1.5:1.5, 97.5:0.5:2, 97.5:1:1.5, 97.5:1.5:1, 98:0.5:1.5 or 98:1:1, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.

[0113] In some embodiments, the second active material layer 3 further includes a second conductive agent and a second binder, and the mass ratio of the second active material to the second conductive agent to the second binder is (94-97): (1.5-3.5): (1-3), 94:3.5:2.5, 94:3:3, 94.5:3.5:2, 94.5:3:2.5, 94.5:2.5:3, 95:3.5:1.5, 95:3:2, 95:2.5:2.5, 95:2:3, 95.5:3.5:1, 95.5:3:1.5, 95.5:2.5:2, 95.5:2:2.5, 95.5:1.5:3, 96:3:1, 96:2.5:1.5, 96:2:2, 96:1.5:2.5, 96.5:2.5:1, 96.5:2:1.5, 96.5:1.5:2, 97:2:1 or 97:1.5:1.5, but not limited to the listed ratios, other ratios not listed within the ratio range are also applicable.

[0114] In some embodiments, the third active material layer 4 also includes a third conductive agent and a third binder, and the mass ratio of the third active material to the third conductive agent to the third binder is (96~98):(0.5~1.5):(1~3), for example, 96:1:3, 96:1.5:2.5, 96.5:0.5:3, 96.5:1:2.5, 96.5:1.5:2, 97:0.5:2.5, 97:1;2, 97:1.5:1.5, 97.5:0.5:2, 97.5:1:1.5, 97.5:1.5:1, 98:0.5:1.5 or 98:1:1, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.

[0115] In certain embodiments, the first conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0116] In certain embodiments, the first conductive agent is selected from conductive carbon black.

[0117] In certain embodiments, the first binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0118] In certain embodiments, the first binder is selected from a composite material of polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber.

[0119] In certain embodiments, the first binder is selected from a composite material of polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 0.25:0.35:0.4.

[0120] In certain embodiments, the second conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0121] In certain embodiments, the second conductive agent is selected from conductive carbon black.

[0122] In certain embodiments, the second binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0123] In certain embodiments, the second binder is selected from a composite material of polyacrylic acid and carboxymethyl cellulose.

[0124] In certain embodiments, the second binder is selected from a composite material of polyacrylic acid and carboxymethyl cellulose in a mass ratio of 0.35:0.65.

[0125] In certain embodiments, the third conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite.

[0126] In certain embodiments, the third conductive agent is selected from carbon nanotubes.

[0127] In certain embodiments, the third binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

[0128] In certain embodiments, the third binder is selected from a composite material of polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber.

[0129] In certain embodiments, the third binder is selected from a composite material of polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 0.25:0.4:0.35.

[0130] The second aspect of the present invention provides a method for preparing the negative electrode sheet according to the first aspect of the present invention, comprising the following steps:

[0131] S0: preparing a slurry of the first active material layer 2: mixing the first active material, the first conductive agent, and the first binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry of the first active material layer 2;

[0132] Preparing a slurry for the second active material layer 3: mixing the second active material, the second conductive agent, and the second binder in a mass ratio of (94-97): (1.5-3.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the second active material layer 3;

[0133] Preparing a slurry for the third active material layer 4: mixing the third active material, the third conductive agent, and the third binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the third active material layer 4;

[0134] S1: coating the prepared slurry of the first active material layer 2 on the current collector 1, drying and rolling after coating to obtain an intermediate structure A;

[0135] S2: coating the prepared second active material layer 3 slurry onto the intermediate structure A obtained in step S1, and after coating, drying and rolling to obtain the intermediate structure B;

[0136] S3: coating the prepared slurry of the third active material layer 4 onto the intermediate structure B obtained in step S2. After coating, drying and rolling are performed to obtain the negative electrode sheet.

[0137] In some embodiments, in step S0, the first active material, the first conductive agent, and the first binder are mixed in a mass ratio of 96:1:3, 96:1.5:2.5, 96.5:0.5:3, 96.5:1:2.5, 96.5:1.5:2, 97:0.5:2.5, 97:1;2, 97:1.5:1.5, 97.5:0.5:2, 97.5:1:1.5, 97.5:1.5:1, 98:0.5:1.5 or 98:1:1, but is not limited to the listed ratios, and mixing in other mass ratios not listed within the ratio range is also applicable.

[0138] In some embodiments, in step S0, the second active material, the second conductive agent, and the second binder are arranged in the ratio of 94:3.5:2.5, 94:3:3, 94.5:3.5:2, 94.5:3:2.5, 94.5:2.5:3, 95:3.5:1.5, 95:3:2, 95:2.5:2.5, 95:2:3, 95.5:3.5:1, 95.5:3:1.5, 95.5:2.5: 2. The mixture may be mixed in a mass ratio of 95.5:2:2.5, 95.5:1.5:3, 96:3:1, 96:2.5:1.5, 96:2:2, 96:1.5:2.5, 96.5:2.5:1, 96.5:2:1.5, 96.5:1.5:2, 97:2:1 or 97:1.5:1.5, but the mixture is not limited to the listed ratios and may be mixed in a mass ratio within the ratio range not listed.

[0139] In some embodiments, in step S0, the third active material, the third conductive agent, and the third binder are mixed in a mass ratio of 96:1:3, 96:1.5:2.5, 96.5:0.5:3, 96.5:1:2.5, 96.5:1.5:2, 97:0.5:2.5, 97:1;2, 97:1.5:1.5, 97.5:0.5:2, 97.5:1:1.5, 97.5:1.5:1, 98:0.5:1.5 or 98:1:1, but are not limited to the listed ratios, and mixing in other mass ratios not listed within the ratio range is also applicable.

[0140] In certain embodiments, in step S1, the mass of deionized water added is 10% of the total mass of the first active material layer slurry.

[0141] In certain embodiments, in step S2, the mass of deionized water added is 12% of the total mass of the second active material layer slurry.

[0142] In certain embodiments, in step S3, the mass of deionized water added is 15% of the total mass of the third active material layer slurry.

[0143] In certain embodiments, in step S1, the coating method is extrusion coating.

[0144] In certain embodiments, in step S2, the coating method is extrusion coating.

[0145] In certain embodiments, in step S3, the coating is performed by extrusion coating.

[0146] In certain embodiments, in step S3, during the coating process, the slurry discharge amount on both sides along the width direction of the current collector 1 is controlled to be smaller than the slurry discharge amount in the middle portion.

[0147] In some embodiments, the compaction density of the first active material layer 2 is 1.0-1.3 g / cm 3 , for example 1.0g / cm 3 , 1.1 g / cm 3 , 1.2 g / cm 3 or 1.3 g / cm 3 ; The compaction density of the first active material layer 2 is controlled within the above range. The porosity of the first active material is large, and the space reserved between particles is large, which makes it easier to alleviate the downward force of silicon expansion and is also beneficial to lithium ion transmission, thereby effectively ensuring the stability of battery performance.

[0148] In some embodiments, the compaction density of the second active material layer 3 is 1.3-1.5 g / cm 3 , for example 1.3 g / cm 3 , 1.4 g / cm 3 or 1.5 g / cm 3 The compaction density of the second active material layer 3 is controlled within the above range, which is lower than the crushing and compaction of the silicon material, and can reduce the distance between silicon and silicon, so that the electrolyte infiltration is less, and the ability of lithium ions to be deintercalated on the surface and inside of the silicon is slowed down, thereby alleviating silicon expansion, which can effectively ensure the stability of battery performance.

[0149] In some embodiments, the compaction density of the third active material layer 4 is 1.0-1.3 g / cm 3 , for example 1.0g / cm 3 , 1.1 g / cm 3 , 1.2 g / cm 3 or 1.3 g / cm 3 The compaction density of the third active material layer 4 is controlled within the above range, which plays the same role as the first active layer and is also conducive to the rapid deintercalation of lithium ions, thereby effectively ensuring the stability of battery performance.

[0150] In some embodiments, the compaction density of the negative electrode plate is 1.5-1.6 g / cm 3 The overall compaction of the negative electrode plate is controlled within the above range, so that the three layers of active material cooperate with each other, which can effectively alleviate the longitudinal expansion of silicon along the thickness direction and improve the electrochemical performance, safety performance and service life of the battery.

[0151] A third aspect of the present invention provides a battery, characterized in that the battery comprises the negative electrode sheet described in the first aspect of the present invention or the negative electrode sheet prepared by the preparation method described in the second aspect of the present invention.

[0152] It should be understood that since the battery provided in the present application includes the negative electrode plate described in the first aspect of the present invention or includes the negative electrode plate prepared by the preparation method described in the second aspect of the present invention, the beneficial effects of the negative electrode plate described in any of the above embodiments are applicable to the battery.

[0153] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0154] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments. Example 1

[0155] 1. Preparation of negative electrode sheet:

[0156] (1) Preparation of the first active material layer slurry: soft carbon, conductive carbon black, polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber were mixed in a mass ratio of 97:1:0.5:0.7:0.8, and deionized water accounting for 10% of the total mass of the first active material layer slurry was added and stirred to form a first active material layer slurry that was mixed evenly and stably;

[0157] Preparation of the second active material layer slurry: After mixing a silicon-carbon material doped with 30% silicon, conductive carbon black, carboxymethyl cellulose and polyacrylic acid in a mass ratio of 95.5:2.5:1.3:0.7, adding 12% of the total mass of the second active material layer slurry with deionized water and stirring to form a uniformly mixed and stable second active material layer slurry;

[0158] Preparation of the third active material layer slurry: Mix the hard carbon material with soft carbon coated on the surface: carbon nanotubes: polyacrylic acid: carboxymethyl cellulose: styrene-butadiene rubber in a mass ratio of 97:1:0.5:0.8:0.7, add 15% of the total mass of the third active material layer slurry of deionized water and stir to form a uniformly mixed and stable bottom negative electrode slurry.

[0159] (2) The prepared first active material layer slurry is applied to a copper foil by extrusion coating. After drying and rolling, an intermediate structure A is obtained. The width L1 of the coated first active material layer is 104 mm.

[0160] (3) The prepared second active material layer slurry is applied to the intermediate structure A by extrusion coating. After drying and rolling, the intermediate structure B is obtained. The width L2 of the second active material layer obtained by coating is 94 mm. The first active material layer and the second active material layer have a width difference on both sides, and the width difference L on both sides is 差 Equal, both 5mm;

[0161] L 差 The calculation method is L 差 =1 / 2(L1-L2).

[0162] (4) The prepared third active material layer slurry is coated on the middle structure B, and the slurry discharge amount on both sides is controlled to be smaller than the slurry discharge amount in the middle. After drying, a negative electrode roll is obtained, and after rolling, a negative electrode sheet with a trapezoidal film surface is obtained. The top layer width L of the coated third active material layer is 3顶 101mm, bottom width L 3底 It is 106mm.

[0163] 2. Preparation of positive electrode

[0164] The positive electrode active material uses nickel-cobalt-manganese ternary material, the conductive agent uses a composite material of conductive carbon black and carbon nanotubes, and the binder uses polyvinylidene fluoride. The positive electrode active material, conductive agent, and binder are mixed in a ratio of 96.5:1.5:2, and after the slurry is mixed, NMP is added and stirred into a uniform and stable positive electrode slurry; the positive electrode slurry is applied to the aluminum foil as the positive electrode current collector by transfer coating, and the positive electrode roll is obtained after drying; after rolling, the positive electrode sheet is obtained.

[0165] 3. Isolation film

[0166] The isolation film uses a polypropylene film as the base film, the base film thickness is 9 μm, a PVDF layer with a thickness of 3 μm is coated on both sides, and then an aluminum oxide layer with a thickness of 3 μm is gravure coated.

[0167] 4. Battery Cell

[0168] The positive electrode sheet, the separator, and the negative electrode sheet are arranged in sequence and assembled by winding to obtain a battery cell.

[0169] 5. Electrolyte

[0170] Dissolve LiPF6 in a mixed solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a ratio of 1.5:1:0.5, and mix well to obtain an electrolyte; wherein the concentration of LiPF6 is 1.2 mol / L;

[0171] 6. Battery Assembly

[0172] The electrolyte is injected into the dry battery cell, and a lithium-ion soft-pack battery is obtained after formation and capacity separation. Example 2

[0173] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0174] The width L1 of the first active material layer obtained in step (2) is 104 mm; the width L2 of the second active material layer obtained in step (3) is 98 mm. The width difference L 差 is 3mm; L in step (4) 3顶 The width is 103mm, L 3底 The width is 106mm.

[0175] The other steps are the same as those in Example 1. Example 3

[0176] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0177] The width L1 of the first active material layer obtained in step (2) is 105 mm; the width L2 of the second active material layer obtained in step (3) is 91 mm. The width difference L 差 is 7mm; L in step (4) 3顶 The width is 99mm, L 3底 The width is 107mm.

[0178] The other steps are the same as those in Example 1. Example 4

[0179] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0180] The width L1 of the first active material layer obtained in step (2) is 104 mm; the width L2 of the second active material layer obtained in step (3) is 100 mm. The width difference L 差 is 2mm; L in step (4) 3顶 The width is 103mm, L 3底 The width is 106mm.

[0181] The other steps are the same as those in Example 1. Example 5

[0182] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0183] The width L1 of the first active material layer obtained in step (2) is 106 mm; the width L2 of the second active material layer obtained in step (3) is 96 mm. The width difference L差 is 5mm; L in step (4) 3顶 The width is 102mm, L 3底 The width is 108mm.

[0184] The other steps are the same as those in Example 1. Example 6

[0185] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0186] The width L1 of the first active material layer obtained in step (2) is 107 mm; the width L2 of the second active material layer obtained in step (3) is 87 mm. The width difference L 差 is 10 mm; L in step (4) 3顶 The width is 95mm, L 3底 The width is 109m.

[0187] The other steps are the same as those in Example 1. Example 7

[0188] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0189] The width L1 of the first active material layer obtained in step (2) is 105 mm; the width L2 of the second active material layer obtained in step (3) is 89 mm. The width difference L 差 is 8mm; L in step (4) 3顶 The width is 97mm, L 3底 The width is 107mm.

[0190] The other steps are the same as those in Example 1. Example 8

[0191] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0192] The width L1 of the first active material layer obtained in step (2) is 104 mm; the width L2 of the second active material layer obtained in step (3) is 96 mm. The width difference L 差 is 4 mm; L in step (4) 3顶 The width is 102mm, L 3底 The width is 107mm.

[0193] The other steps are the same as those in Example 1. Example 9

[0194] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0195] The width L1 of the first active material layer obtained in step (2) is 104 mm; the width L2 of the second active material layer obtained in step (3) is 90 mm, with a width difference of 7 mm; the width L2 of the second active material layer obtained in step (4) is 90 mm. 3顶 The width is 102mm, L 3底 The width is 105mm.

[0196] The other steps are the same as those in Example 1. Example 10

[0197] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0198] The width L1 of the first active material layer obtained in step (2) is 106 mm; the width L2 of the second active material layer obtained in step (3) is 100 mm, with a width difference of 3 mm; the width L2 of the second active material layer obtained in step (4) is 106 mm. 3顶 The width is 102mm, L 3底 The width is 109mm.

[0199] The other steps are the same as those in Example 1. Comparative Example 1

[0200] The method for preparing the negative electrode sheet in this embodiment is different from that in Embodiment 1 in that:

[0201] The width L1 of the first active material layer obtained in step (2) is 104 mm; the width L2 of the second active material layer obtained in step (3) is 104 mm. The width difference L 差 is 0mm; L in step (4) 3顶 The width is 104mm, L 3底 The width is 104mm.

[0202] The other steps are the same as those in Example 1.

[0203] Performance Testing

[0204] 1. Capacity test: In a 25°C incubator, charge the battery to 3.65 V at a constant current rate of 0.33 C, charge the battery at a constant voltage of 3.65 V until the current reaches 0.05 C, let it stand for 30 minutes, then discharge the battery to 2.5 V at a constant current of 0.33 C, let it stand, and cycle the battery for two weeks. The capacity in the last week is the actual capacity C0 (i.e., discharge capacity) of the battery.

[0205] 2. Cycle performance test: In a 45℃ temperature box, use 1 C0 rate constant current to charge to 3.65V, 3.65V constant voltage to charge to the current cutoff of 0.05 C0, stand for 30 minutes, 1 C0 constant current discharge to 2.5V, stand for 30 minutes, and cycle in sequence. Compare the capacity of each cycle with the first cycle at the beginning of the cycle to obtain the cycle capacity retention rate. The number of cycles corresponding to the capacity retention rate of 80% is the number of high-temperature cycles.

[0206] 3. Full charge rebound rate test: Use 0.33 C0 constant current to charge to 3.65 V, 3.65V constant voltage to charge to 0.05 C0, disassemble and measure the thickness of the negative electrode, measure the edge and middle area respectively, select 6 points on the edge of the electrode, and take the average value H 平 , rebound rate H 边 =(H 平 -H 初 ) / (H 初 -H cu ). Among them, H 初 is the designed thickness of the negative electrode sheet, H cu is the thickness of the copper foil.

[0207] The test results are shown in Table 1.

[0208] Table 1

[0209]

[0210] According to the comparative data of Examples 1 to 10 and Comparative Example 1 in Table 1, the negative electrode plate provided by the embodiment of the present invention, by selecting soft carbon as the active material material of the first active material layer in the negative electrode plate and using a hard carbon material coated with soft carbon on the surface as the active material material of the third active material layer, alleviates the downward squeezing force of silicon expansion in the second active material layer, improves the electron conduction and lithium ion transmission capacity, reduces the direct contact between silicon and the electrolyte to reduce the occurrence of side reactions; and by controlling the width of the second active material layer to be narrower than the width of the first active material layer and the top width of the third active material layer, setting a width difference between the edge of the first active material layer and the edge of the second active material layer, and providing a slope on both sides of the third active material layer to provide silicon with space for lateral expansion, effectively alleviates the bulging edge caused by the lateral expansion of silicon particles at the edge of the second active material layer, and improves the electrochemical performance, safety stability and service life of the prepared battery, which is specifically manifested in that the full charge rebound rate of the negative electrode plate is effectively reduced and the number of high-temperature cycles of the prepared battery is increased.

[0211] It can be seen from the data in Table 1 that the discharge capacity in the comparative example is higher than that in the embodiment. This is because the width of L2 of the negative electrode plate in comparative example 1 is wider than that in other embodiments, which is 104 mm. Therefore, more second layer active material (i.e., silicon-carbon material) is required. Since the gram capacity of silicon is higher than that of carbon material, the discharge capacity in comparative example 1 is only slightly higher than that in the embodiment.

[0212] It can be seen from the data in Table 1 that, compared with Comparative Example 1 in which the width of the first active material layer and the second active material layer in the negative electrode sheet are equal, the negative electrode sheets in Examples 1 to 10 of the present application with a preset width difference between the two layers have a lower electrode sheet full charge rebound rate, and the full charge rebound rate is reduced by at least 8.79% compared with Comparative Example 1. Among them, the full charge rebound rate of the negative electrode sheet in Example 6 is reduced by 16.9% compared with the negative electrode sheet in Comparative Example 1, which can effectively improve the safety and service life of the prepared battery.

[0213] It can be seen from the data in Table 1 that compared with Comparative Example 1, the negative electrode sheets with a preset width difference between the first active material layer and the second active material layer in Examples 1 to 10 of the present application have more excellent high-temperature cycle performance, among which the number of battery cycles prepared by the negative electrode sheet in Example 6 increased by 100 compared with Comparative Example 1, and the high-temperature cycle life was significantly improved by 18.18%, which effectively improved the electrochemical performance and service life of the battery.

[0214] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector (1), and a first active material layer (2), a second active material layer (3) and a third active material layer (4) arranged in sequence on at least one side surface of the current collector (1) in a thickness direction; The width of the second active material layer (3) is smaller than that of the first active material layer (2), and the third active material layer (4) covers the first active material layer (2) and the second active material layer (3) at least in the width direction of the current collector (1); The first active material layer (2) comprises a first active material, and the first active material is soft carbon; The second active material layer (3) comprises a second active material, and the second active material is a silicon-carbon material; The third active material layer (4) comprises a third active material, wherein the third active material is a hard carbon material with soft carbon coated on the surface; The negative electrode plate satisfies L 3底 >L1>L 3顶 >L2; Wherein, L1 is the width of the first active material layer (2); L2 is the width of the second active material layer (3); 3顶 is the top width of the third active material layer (4); the L 3底 is the bottom width of the third active material layer (4).

2. The negative electrode sheet according to claim 1, characterized in that: On both sides of the current collector (1) in the width direction, there is a preset width difference between the edge of the first active material layer (2) and the edge of the second active material layer (3); and / or, Along the width direction of the current collector (1), the thickness of the third active material layer (4) gradually decreases from a preset position toward the edge of the negative electrode sheet, and the projection of the preset position in the thickness direction of the current collector (1) is located between the edge of the first active material layer (2) and the edge of the second active material layer (3).

3. The negative electrode sheet according to claim 2, characterized in that: On both sides of the width direction of the current collector (1), the preset width difference on both sides of the second active material layer (3) is equal; and the negative electrode sheet satisfies: L 差 =1 / 2(L1-L2); where L 差 is the preset width difference.

4. The negative electrode sheet according to claim 1, characterized in that: The D50 of the first active material is in the range of 5 to 25 μm; and / or the D50 of the active material of the second active layer is in the range of 3 to 15 μm; and / or the D50 of the active material of the third active layer is in the range of 2 to 18 μm.

5. The negative electrode sheet according to claim 1, characterized in that: The current collector (1) is selected from one or more of copper foil, aluminum foil and nickel foil; and / or, The soft carbon in the first active material layer (2) and the soft carbon in the third active material layer (4) are each independently selected from one or more of carbon fibers, carbon microspheres, graphitized mesophase carbon microspheres, petroleum coke and needle coke; and / or, The silicon-carbon material is selected from silicon-carbon materials containing 20% ​​to 40% silicon; and / or, The hard carbon is selected from one or more of resin carbon, organic polymer pyrolytic carbon and carbon black.

6. The negative electrode sheet according to claim 1, characterized in that: The first active material layer (2) further comprises a first conductive agent and a first binder, wherein the mass ratio of the first active material to the first conductive agent to the first binder is (96-98): (0.5-1.5): (1-3); and / or, The second active material layer (3) further comprises a second conductive agent and a second binder, wherein the mass ratio of the second active material to the second conductive agent to the second binder is (94-97): (1.5-3.5): (1-3); and / or, The third active material layer (4) further comprises a third conductive agent and a third binder, and the mass ratio of the third active material to the third conductive agent to the third binder is (96-98): (0.5-1.5): (1-3).

7. The negative electrode sheet according to claim 6, characterized in that: The first conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite; and / or, The first binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber; and / or, The second conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite; and / or, The second binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber; and / or, The third conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, carbon nanofibers, graphene, and conductive graphite; and / or, The third binder is selected from one or more of polyacrylic acid, carboxymethyl cellulose, polyaniline, and styrene-butadiene rubber.

8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: The following steps are involved: S0: preparing a slurry of the first active material layer (2): mixing the first active material, the first conductive agent, and the first binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry of the first active material layer (2); Preparing a slurry for the second active material layer (3): mixing the second active material, the second conductive agent, and the second binder in a mass ratio of (94-97): (1.5-3.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the second active material layer (3); Preparing a slurry for the third active material layer (4): mixing the third active material, the third conductive agent, and the third binder in a mass ratio of (96-98): (0.5-1.5): (1-3), adding deionized water and stirring to form a uniform and stable slurry for the third active material layer (4); S1: coating the prepared slurry of the first active material layer (2) onto the current collector (1), and after coating, drying and rolling to obtain an intermediate structure A; S2: coating the prepared second active material layer (3) slurry onto the intermediate structure A obtained in step S1, and after coating, drying and rolling to obtain the intermediate structure B; S3: coating the prepared slurry of the third active material layer (4) onto the intermediate structure B obtained in step S2. After coating, drying and rolling are performed to obtain the negative electrode sheet.

9. The preparation method according to claim 8, characterized in that: The compaction density of the first active material layer (2) is 1.0-1.3 g / cm 3 The compaction density of the second active material layer (3) is 1.3-1.5 g / cm 3 The compaction density of the third active material layer (4) is 1.0-1.3 g / cm 3 The compaction density of the negative electrode plate is 1.5-1.6 g / cm 3 .

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 7 or the negative electrode sheet prepared by the preparation method according to claim 8 or 9.